2016
DOI: 10.1111/mec.13881
|View full text |Cite
|
Sign up to set email alerts
|

Pooled ecotype sequencing reveals candidate genetic mechanisms for adaptive differentiation and reproductive isolation

Abstract: The early stages of speciation are often characterized by the formation of partially reproductively isolated ecotypes, which evolve as a by-product of divergent selective forces that are endemic to different habitats. Identifying the genomic regions, genes and ultimately functional polymorphisms that are involved in the processes of ecotype formation is inherently challenging, as there are likely to be many different loci involved in the process. To localize candidate regions of the genome contributing to ecot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(102 citation statements)
references
References 112 publications
(281 reference statements)
6
96
0
Order By: Relevance
“…WGR has been used for the discovery and mapping of the genetic basis of phenotypic traits with adaptive importance (Table ), for instance, the beak shape of Darwin finches (huWGR; Lamichhaney et al, ) or the age at maturity in Atlantic salmon (huWGR: Barson et al, ; Pool‐seq: Ayllon et al, ). Other examples, all based on Pool‐seq data, include: the red beak colour in canaries (Lopes et al, ), circadian timing in midges (Kaiser et al, ), genes affecting brain and neuronal development associated with domestication of rabbits (Carneiro et al, ), genes associated with breeding related traits of pathogen resistance and reproductive ability in two highly inbred chicken lines (Fleming et al, ), candidate genes potentially driving the morphological, life history and salt tolerance differences between ecotypes of the yellow monkey‐flower plant (Gould, Chen, & Lowry, ), and immune‐related genes in Atlantic salmon (Kjærner‐Semb et al, ). Similarly, studies based on lcWGR data include the detection of a recent partial barrier (large inversion) to gene flow between subgroups of the mosquito Anopheles gambiae s.l.…”
Section: Applications Of Wgr In Conservation and Managementmentioning
confidence: 99%
“…WGR has been used for the discovery and mapping of the genetic basis of phenotypic traits with adaptive importance (Table ), for instance, the beak shape of Darwin finches (huWGR; Lamichhaney et al, ) or the age at maturity in Atlantic salmon (huWGR: Barson et al, ; Pool‐seq: Ayllon et al, ). Other examples, all based on Pool‐seq data, include: the red beak colour in canaries (Lopes et al, ), circadian timing in midges (Kaiser et al, ), genes affecting brain and neuronal development associated with domestication of rabbits (Carneiro et al, ), genes associated with breeding related traits of pathogen resistance and reproductive ability in two highly inbred chicken lines (Fleming et al, ), candidate genes potentially driving the morphological, life history and salt tolerance differences between ecotypes of the yellow monkey‐flower plant (Gould, Chen, & Lowry, ), and immune‐related genes in Atlantic salmon (Kjærner‐Semb et al, ). Similarly, studies based on lcWGR data include the detection of a recent partial barrier (large inversion) to gene flow between subgroups of the mosquito Anopheles gambiae s.l.…”
Section: Applications Of Wgr In Conservation and Managementmentioning
confidence: 99%
“…In plants, ecotype formation is frequently triggered by the colonization and subsequent adaptation to different substrates (e.g. Turner et al, ; Andrew et al, ; Arnold et al, ; Gould et al, ). Our genome‐wide association study identified SNPs, genes and gene ontology terms directly or indirectly associated with divergent adaptation to rock and sand substrates in A. lyrata .…”
Section: Discussionmentioning
confidence: 99%
“…Andrew, Kane, Baute, Grassa, & Rieseberg, ; Arnold et al, ; Gould, Chen, & Lowry, ; Turner, Bourne, Von Wettberg, Hu, & Nuzhdin, ). Recent research focused on understanding the genomic underpinning of such substrate‐related ecotypes, with an emphasis on outcrossing taxa (Andrew et al, ; Arnold et al, ; Gould et al, ; Turner et al, ). However, mating system is predicted to have a strong impact on the genetics of ecotype formation as well as the rate of evolution (Hartfield, Bataillon, & Glémin, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gould et al . () applied a Pool‐Seq approach to localize candidate regions of the genome contributing to ecotype formation in coastal/inland ecotypes of the yellow monkeyflower, Mimulus guttatus . They discovered genetic divergence in association with two chromosomal inversions, suggesting that frequencies of inversion heterokaryotypes are strongly differentiated between the ecotypes in addition to genomewide candidate genes potentially driving the morphological, life history and salt tolerance differences between the ecotypes.…”
Section: Genomic Adaptationmentioning
confidence: 99%